Permanent Neonatal Diabetes Mellitus Due to an ABCC8 Mutation: A Case Report - Abraham, Nithya; Ahamed, Anish; Unnikrishnan, Ambika Gopalakrishnan; Kumar, Harish; Ellard, Sian (JOP. Journal of the Pancreas, 2014)
Context Neonatal diabetes is a rare disorder with an incidence of about 1 in 100,000 live births. It is defined as diabetes diagnosed in the first 6 months of life and it is vital to differentiate this entity from type 1 diabetes to enable accurate diagnosis, prognosis, genetic counseling and treatment. Case report We describe a case of permanent neonatal diabetes mellitus due to a novel mutation affecting the ABCC8 gene that encodes the SUR1 subunit of potassium ATP channel (KATP). Conclusion This genetic diagnosis has therapeutic implications as patients can switch from insulin therapy to sulphonylurea, as described in this case report. Image: Amrita Institute of Medical Sciences. Cochin, India